Effect of inclusion of citric acid and Lutrol® F-68 on ziprasidone and β-cyclodextrin complexation: Characterization, solubility and dissolution studies - Londhe, Vaishali Yogesh; Krishnan, Sreevidya Ramesh (European Journal of Chemistry, 2020)
Ziprasidone (ZPR) is an antipsychotic agent having less solubility. It is used for the treatment of schizophrenia. Complexation of hydrophobic drugs with cyclodextrins leads to enhanced solubility and dissolution. In this study, inclusion complexes were prepared by different methods, using ZPR, β-cyclodextrin (β-CD), and different auxiliary agents like hydrophilic polymer and hydroxy acid (1:1:0.5) to improve the aqueous solubility. The characterization of the ternary complexes was carried out using solubility study, Differential scanning calorimetry (DSC), Powder X-ray diffraction (PXRD), Fourier transformation infrared spectroscopy (FT-IR) and in vitro dissolution studies. DSC, XRD, and FT-IR studies showed interaction in drug, cyclodextrin, and auxiliary agents which are confirmed by enhancement of solubility and dissolution. Spray-dried dispersion showed less crystallinity and higher solubility as compared to the kneading method for both citric acid and Lutrol® F-68. Thus, the investigation concludes that the presence of the auxiliary agent has a synergistic action on complexation with cyclodextrin, which helps to modify the physicochemical properties of the drug.